Where you are affects what you can easily imagine: Environmental geometry elicits sensorimotor interference in remote perspective taking - Riecke, Bernhard E.; McNamara, Timothy P. (Cognition, 2017)
Imagined perspective switches are notoriously difficult, a fact often ascribed to sensorimotor interference between one’s to-be-imagined versus actual orientation. Here, we demonstrate similar interference effects, even if participants know they are in a remote environment with unknown spatial relation to the learning environment. Participants learned 15 target objects irregularly arranged in an office from one orientation (0°, 120°, or 240°). Participants were blindfolded and disoriented before being wheeled to a test room of similar geometry (exp.1) or different geometry (exp.2). Participants were seated facing 0, 120°, or 240°, and asked to perform judgments of relative direction (JRD, e.g., imagine facing “pen”, point to “phone”). JRD performance was improved when participants’ to-be-imagined orientation in the learning room was aligned with their physical orientation in the current (test) room. Conversely, misalignment led to sensorimotor interference. These concurrent reference frame facilitation/interference effects were further enhanced when the current and to-be-imagined environments were more similar. Whereas sensorimotor alignment improved absolute and relative pointing accuracy, sensorimotor misalignment predominately increased response times, supposedly due to increased cognitive demands. These sensorimotor facilitation/interference effects were sustained and could not be sufficiently explained by initial retrieval and transformation costs. We propose that facilitation/interference effects occurred between concurrent egocentric representations of the learning and test environment in working memory. Results suggest that merely being in a rectangular room might be sufficient to automatically re-anchor one’s representation and thus produce orientation-specific interference. This should be considered when designing perspective-taking experiments to avoid unintended biases and concurrent reference frame alignment effects.
Keywords: Concurrent reference frame alignment/interference; DG2019; Perspective-taking; Reference frame conflicts; Riecke; Riecke_2017; Sensorimotor interference; Spatial cognition; Spatial memory; Spatial updating; bernhard-riecke; fullProfPromotionPackage; journalPaper; spatial cognition; timothy-mcnamara